Five-Year Trends in Payments for Neurologist-Prescribed Drugs in Medicare Part D. (20th April 2021) - de Havenon, Adam; Delic, Alen; Dehoney, Sarah; Whetman, Presley; Sheibani, Nazanin; Callaghan, Brian; Ney, John; Esper, Gregory J.; Magliocco, Brandon; Nair, Kavita V.
Abstract : Objective: To determine whether there was an increase in payments for neurologist-prescribed drugs, we performed a retrospective analysis of prescription claims in the Medicare Part D Prescriber Public Use Files from 2013 to 2017. Methods: We included claims prescribed by providers with the taxonomy "neurology" and included drugs present in all 5 years. Drugs were designated in 2013 as generic (GEN), brand name only (BNO), and brand name prescribed even though a generic equivalent is available (BNGE). To observe payment trends, the percentage change in the per claim payment was compared between drug classes. Results: We included 520 drugs, of which 322 were GEN, 61 were BNO, and 137 were BNGE, representing 90, 716, 536 claims and generating payments of $26, 654, 750, 720. While the number of claims from 2013 to 2017 increased only 7.6%, the total payment increased 50.4%. Adjusted for inflation, claim payments for GEN drug increased 0.6%, compared to significant increases in BNO and BNGE drugs of 42.4% and 45.0% ( p trend < 0.001). The percentage of overall GEN claims increased from 81.9% to 88.0%, BNO increased from 4.9% to 6.2%, and BNGE decreased from 13.3% to 5.8%. Neuroimmunology/multiple sclerosis drugs represented >50% of the total payments despite being only 4.3% of claims. Conclusions: Payments for neurologist-prescribed brand name, but not generic, drugs in Medicare Part D increased consistently and well above inflation from 2013 to 2017. Unless the overall trend stabilizes or is reversed or high cost-to-claim drugs are addressed, this trend will place an increasing burden on the neurologic Medicare budget.